Smart medical English pedagogy on a smart teaching platform - Wang, Xianyun; Hamat, Afendi Bin; Shi, Ng Lay (Edelweiss Applied Science and Technology, 2024)
The widespread adoption of smart mobile devices has sparked significant innovations in China’s smart education landscape in recent years. Smart teaching platforms play a pivotal role in shaping the dynamics of smart teaching. This study aimed to enhance medical English pedagogy by implementing smart teaching on the smart teaching platform (Xuexitong). The researchers divided their 178 nursing-majored students into two control classes and two experimental classes to evaluate the effectiveness of smart teaching. Traditional classroom instruction was adopted in the control classes while smart pedagogy was applied in the experimental classes. After a semester-long teaching experiment, two assessments were conducted: a comparison of exam scores and a course feedback survey. The findings revealed that students in the experimental classes significantly outperformed the control group in these two assessments. This highlights the substantial effectiveness of smart medical English pedagogy demonstrating its ability to enhance students’ language proficiency and comprehension in medical contexts far beyond traditional teaching methods. The study concluded that smart teaching can significantly improve teaching outcomes and facilitate pedagogical innovations among new technological advancements. These insights offer valuable guidance for future research to enhance the integration of smart mobile technologies with smart language pedagogy.